SHM_415360_HST_3D Lihult Stone Axe - Lernestål, Erik; Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a Mesolithic Lihult stone axe collected in Dalsland and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=670

Link to Sök I Samlingarna

https://samlingar.shm.se/object/006BBEB4-4B0E-4C7E-8153-3EAF4B6B347A
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; Archaeology/history; History and archaeology; Dynamic Collections; Dalsland; Swedish Mesolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi